Isolation and cahracterization of antibacterial peptides from hemolymph of the soft tick, Ornithodoros savignyi - Neitz, A.W.H. (Albert Walter Herman) (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2002.